'I think they need to rethink their concept!': examining teachers' sense of preparedness to deal with student heterogeneity. Issue 3 (26th May 2020) - Pozas, Marcela; Letzel, Verena
ABSTRACT: Following a mixed-method approach research design, this paper reports on two studies that seek to investigate teachers' sense of preparedness to deal with student heterogeneity and its effect on their differentiated instructional practice. The first study uses nationally representative data from the National Educational Panel Study in Germany ( N = 677), while the second study analyses, on a micro-level, interview responses of 18 secondary school teachers. Findings from both studies reveal the overall significance of teachers' preparedness and collaboration as a means to deal with student heterogeneity and effectively implement DI. Moreover, results provide important information into teachers' training needs. Implications of the results and further research are discussed.